DIRECTIONAL 1900 MHZ SQUARE PATCH RING SLOT MICROSTRIP ANTENNA FOR WCDMA - Irfan Mujahidin (Merdeka Malang University, 2018)
Telecommunications systems especially WCDMA networks, require an antenna to convert electromagnetic energy in the air into electrical energy will be processed into the information signal. WCDMA (Wideband Code-Division Multiple Access) network works at a frequency of 1900 MHz with a complicated configuration antenna and has high-cost components. Directional 1900 MHz Square Patch Ring Slot Microstrip Antenna for WCDMA has been proposed. This is a novel technique in telecommunication configuration to make directional antenna use more proper and efficient component by using low cost and easy to find material at 1900 MHz frequency. This compact configuration consists of a single rectangular patch, a substrate, a ground plan and ring slot on the ground plane. This antenna produces an accurate frequency at 1900MHz with the value of -15.19 dB and gains 6.78 dBi at. The overall size of the proposed antenna is 55.7 mm times 49.2 mm with FR4 (Phenolic White Paper) with a dielectric constant value is 4.4. DOI : https://doi.org/10.26905/jeemecs.v1i2.2626 Telecommunications systems especially WCDMA networks, require an antenna to convert electromagnetic energy in the air into electrical energy will be processed into the information signal. WCDMA (Wideband Code-Division Multiple Access) network works at a frequency of 1900 MHz with a complicated configuration antenna and has high-cost components. Directional 1900 MHz Square Patch Ring Slot Microstrip Antenna for WCDMA has been proposed. This is a novel technique in telecommunication configuration to make directional antenna use more proper and efficient component by using low cost and easy to find material at 1900 MHz frequency. This compact configuration consists of a single rectangular patch, a substrate, a ground plan and ring slot on the ground plane. This antenna produces an accurate frequency at 1900MHz with the value of -15.19 dB and gains 6.78 dBi at. The overall size of the proposed antenna is 55.7 mm times 49.2 mm with FR4 (Phenolic White Paper) with a dielectric constant value is 4.4.